Different association between triglyceride-glucose index and mild cognitive impairment in type 2 diabetes mellitus patients with and without diabetic kidney disease - Feng, Songtao; Zhang, Zhen; Gao, Qingyue; Huang, Ling; Zhang, Ya; He, Mengting; Song, Bing; Zhu, Wenwen; Ding, Li (Frontiers in Nutrition, 2025)
AimThe triglyceride-glucose (TyG) index, a surrogate marker reflecting metabolic status related to both glucose and lipid homeostasis, has been implicated in the development of diabetes-related complications, including diabetic kidney disease (DKD). Metabolic disturbances in carbohydrate and lipid pathways have also been linked to impairments in cognitive performance. This study aims to explore the association between TyG levels and the presence of mild cognitive impairment (MCI) among individuals with type 2 diabetes mellitus (T2DM), stratified by DKD status.MethodsA total of 243 patients with T2DM were divided into two subgroups based on cognitive status: those with MCI and those without. Clinical parameters were assessed and compared between the two cohorts. The association between TyG index and cognitive function was analyzed. Furthermore, potential predictors of MCI were explored separately in T2DM patients with and without DKD.ResultsIn individuals with T2DM, those exhibiting MCI (n = 95) showed significantly higher TyG index values in comparison to counterparts with normal cognition (n = 148). Elevated TyG index was linked to reduced performance on the Montreal Cognitive Assessment, a measure of global cognition, as well as diminished scores on both the Verbal Fluency Test and the delayed recall component of the Auditory Verbal Learning Test, which assess executive function and immediate memory, respectively, in patients without DKD. These findings suggest that heightened TyG index may serve as an independent risk indicator for cognitive decline in T2DM individuals without DKD. However, among those with coexisting DKD, no statistically meaningful association between TyG index and cognitive outcomes was observed.ConclusionElevated TyG index levels have been linked to an increased likelihood of MCI, particularly affecting executive function and immediate recall, among individuals with T2DM but without DKD.